Construction of Legal Relations: The nature of the laws of lands (“Landrechten”) during the 13th and 14th centuries - Πάνος Αθανάσιος (Mos Historicus: A Critical Review of European History, 2025)
The legislative innovations during the 13th century within the German Empire are critically presented, focusing on the laws of lands and their evolution until the 14th century. The relationship of Frederic II’s imperial course to the legal theory is examined, then the Mirror Laws of Saxons and Swabians. The institutional architecture of the German Empire is reached through the whole legal development. Historical elements of the relationship between feudalism and legal forms are highlighted.